2021
DOI: 10.31729/jnma.6684
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric Injuries after Hysterectomy in a Tertiary Care Center of Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Pelvic surgery is the most common cause of iatrogenic ureteral injury. The incidence of ureteric injuries varies between skilled and inexperienced surgeons. The study aims to determine the prevalence of ureteric injuries sustained during hysterectomy in a tertiary care center of Nepal. Methods: A descriptive cross-sectional study involving the women attending the gynecological outpatient department of a tertiary care center of Nepal, for various benign and malignant conditions and later on underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The incidence of bladder injury varies depending on the procedure; Wong et al reported an incidence of 0.24% in laparoscopic surgery in benign pathology; Other studies report an incidence of 0.44% in cesarean sections and 1.54% during hysterectomies for benign pathol-Volume 54-Issue 4 DOI: 10.26717/BJSTR.2024.54.008586 ogy [8,9]. Lower urinary tract injuries including bladder injuries are associated with increased morbidity; This includes the formation of fistulas, infections, hydronephrosis and kidney injury, combined with a 60% percentage of reinterventions, with an increase in hospital stay and affecting quality of life [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of bladder injury varies depending on the procedure; Wong et al reported an incidence of 0.24% in laparoscopic surgery in benign pathology; Other studies report an incidence of 0.44% in cesarean sections and 1.54% during hysterectomies for benign pathol-Volume 54-Issue 4 DOI: 10.26717/BJSTR.2024.54.008586 ogy [8,9]. Lower urinary tract injuries including bladder injuries are associated with increased morbidity; This includes the formation of fistulas, infections, hydronephrosis and kidney injury, combined with a 60% percentage of reinterventions, with an increase in hospital stay and affecting quality of life [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[8,12]. One third of ureter injuries are diagnosed intraopera-tively; The rest of the lesions are diagnosed postoperatively, in which the clinical manifestations include fever, peritonitis, paralytic ileus, urinoma, abscess, hematuria, leakage of urine through the vagina, or through drains [1,10]. Early diagnosis of injuries is a priority because it allows early repair with a better prognosis since it minimizes longterm morbidity [5,9,14].…”
Section: Introductionmentioning
confidence: 99%
“…All of the above negatively affects the final outcome of repair procedures, significantly complicating postoperative rehabilitation of patients. The management of UIs established postoperatively, with the subsequent formation of ureteral strictures/obliteration or ureterovaginal fistula, has witnessed constant transformations over the past decade, ranging from the frequently used open approach, to the minimally invasive endourological procedures such as retrograde or antegrade stent insertion, and percutaneous nephrostomy tube placement [12][13][14][15][16]. Coupled with UIs, complications from pelvic surgeries could lead to other lower urinary tract dysfunction, for example, injuries to the pelvic nerves, can cause long-term bladder dysfunction in patients [17,18].…”
Section: Introductionmentioning
confidence: 99%